Impaired diffusing capacity for carbon monoxide is common in critically ill Covid-19 patients at four months post-discharge - E, Ekbom (Respir Med, 2021)
There is limited knowledge about the long-term effects on pulmonary function of COVID-19 in patients that required intensive care treatment. Spirometry and diffusing capacity for carbon monoxide (DLCO) were measured in 60 subjects at 3-6 months post discharge. Impaired lung function was found in 52% of the subjects, with reduced DLCO as the main finding. The risk increased with age above 60 years, need for mechanical ventilation and longer ICU stay as well as lower levels of C-reactive protein at admission. This suggests the need of follow-up with pulmonary function testing in intensive-care treated patients.